Pengaruh Pola Asuh Orang Tua Terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMPN 9 Kota Bogor - Seka Pratama Dewi; Kholil Nawawi; Noor Isna Alfaien (Departement of Mathematics Education, 2023)
Based on the author's observation of class VIII students at SMPN 9 Kota Bogor. Some students still lack interest in Islamic Religious Education subjects. In this case, the need for encouragement from parents in educating and guiding and supervising students to grow and arouse students' interest in learning in Islamic Religious Education subjects, so that the better the parents' parenting style, the higher the students' learning interest in Islamic Religious Education subjects. The purpose of this study was to determine the parenting style applied by parents of students in class VIII SMPN 9 Bogor City, to determine students' learning interest in class VIII SMPN 9 Bogor City and to determine the effect of parenting style on students' interest in learning Islamic religious education in class VIII SMPN 9 Bogor City. The method used in this research is quantitative with a field research approach to obtain or collect information about the influence of parenting styles on students' learning interest in Islamic Religious Education class VIII at SMPN 9 Kota Bogor. Then a simple linear regression test was carried out using SPSS 22 to find out the significant results of the effect of parenting style on students' learning interest in Islamic Religious Education class VIII at SMPN 9 Bogor City with the T test. If T is calculated at a significant level of 0.05% with degrees of freedom (df) = N-2 (81-2) = 79, Tcount = 4.816 > Ttable 1.664. Because Tcount > Ttable, Ho is rejected and Ha is accepted, which means that there is an influence of parenting styles on students' learning interest in class VIII Islamic Religious Education at SMPN 9 Bogor City.